Impacts of Architectural Sights on Anxiety Relief in a High-Density City - Yung-Chia Chiu; Ming-Chyuan Ho; Jui-Che Tu; Yi-Jhen Jhuang (Engineering Proceedings)
Due to rapid urbanization, high-density cities have become a dominant human habitat, and sustainable urban development has become a key concept in urban governance. Thus, it is important to understand the impact of visual elements in urban architecture on stress to make accurate and practical planning and strategies for healthy and sustainable living environments. We examined the designs and features of building facades that alleviate stress and identified measuring metrics for stress relief in viewers. We selected 20 Taiwanese-style public buildings for the examination. To understand the relationship between architecture and stress relief, 70 participants were interviewed in a semi-structured method after showing images of the 20 buildings. We used the semantic differential method and a 7-point image scale to rate stress relief from various architectural styles. The participants found the use of multiple materials or lighting in public buildings interesting but not stress-relieving. A greater amount of cooler and heavier materials made of iron in the building exterior increased stress. This finding offers insights into planning and developing sustainable and psychologically supportive urban environments.